Web information retrieval (IR) interaction / Amirohaime Mahaidin - Mahaidin, Amirohaime (2008)
A good information retrieval (IR) interaction should provide tools to perform searching accurately based on user requirement. There are many website retrieve variant to the same relevant website. To overcome these website variants problems, conflation was introduced. Stemming method was proven to be successful in reducing words with the same stem to a common from and is evidenced by the work of many researchers. Web information interaction retrieves the relevant website to user and applied stemming algorithm. This website project consists of interactive guidance to retrieve the relevant URL. Searching from query given to URL document will retrieve the relevant URL suggestion by expert. The testing is for measuring the recall and precision in retrieve and relevant document. The project testing shown that most of documents retrieved, does not relevant to the queries. As a conclusion we must applied more than one algorithm in term to retrieve relevant document accurately based on user requirement.